Research Landscape of "The Bhagavad Gita": A Bibliometric Visualization Analysis based on Scopus Database - Poologanathan, P. (University of Jaffna, 2025)
This study aims to analyze research trends and perspectives on The Bhagavad Gita based on bibliometric data retrieved from the Scopus database. The Bhagavad Gita, a 700-verse Hindu scripture embedded within the Indian epic Mahabharata, is widely regarded as a life strengthening text. It presents a philosophical and spiritual discourse between Prince Arjuna and the deity Krishna, addressing key concepts such as Dharma, Yoga, and various ethical and metaphysical themes. For this bibliometric analysis, data were collected using the search term "Bhagavad Gita" in article titles, covering the period from 1990 to November 2023. A total of 330 records were identified and analyzed using VOSviewer and Microsoft Excel. The analysis considered multiple parameters, including country-wise distribution, journal-wise publication trends, institutional contributions, subject classifications, keyword occurrences, citation patterns, document types, languages, and authorship trends. The findings indicate that 330 publications were produced over the 33-year period, accruing a total of 1,322 citations, with an average citation count of 4.0 per publication and an h-index of 16. The highest number of publications was recorded in 2023, with 30 articles (9% of the total output). The majority of research contributions fell within the subject area of Arts and Humanities (210 publications, 64%). The United States emerged as the leading contributor to this field, while the most prolific author was Muniapan B., with six publications (2%). This study provides valuable insights for librarians, researchers, and scholars of religion and philosophy, offering a comprehensive overview of the academic discourse surrounding The Bhagavad Gita. The findings serve as a foundation for future scholarly investigations, facilitating further exploration of its philosophical, ethical, and theological dimensions.
Keywords: Bhagavad Gita; Spiritual; Hindu scripture; Dharma; Yoga; Bibliometric